New Product Preannouncement: Phantom Products and the Osborne Effect - Rao, Ram; Turut, Ozge (Management Science, 2019)
The mere preannouncement of a new product can affect consumer choice, thus complicating preannouncement strategy. This is because a preannounced product that is unavailable immediately can still be one of the alternatives in a consumer’s mind at the time of choice. Such unavailable products, also known as phantom products, influence the reference point that consumers compare alternatives to when making a choice, as has been widely demonstrated in experimental studies. Thus, in addition to encouraging consumers to postpone purchase in favor of a future product, preannouncement also changes their preference for the currently available products when consumers do not prefer to postpone. In this paper we explore preannouncement strategy by analyzing a model that incorporates the effect of new product preannouncement (NPP) on consumer preferences and compare the results with a benchmark case in which consumer preferences across the existing products are not influenced by preannouncement. We find that when we take into account the effect of NPP on consumer preferences across the existing products, although postponement of purchase by some consumers remains beneficial, the preference for the current product offering with a lower quality can suffer so much that the significant lowering of current profits is not offset by future gains. Thus, preannouncement may no longer be the optimal strategy for the firm with a lower-quality product, which in turn explains the “Osborne effect.” Our results also challenge the conventional wisdom in new product preannouncement literature. This paper was accepted by Juanjuan Zhang, marketing.